Characterizing nitrogen cycling microorganisms and genes in sediments of the Three Gorges Reservoir - Chang Han; Zhiyuan Chen; Yihui Xiao; Ting Yang; Haoyang Shi; Huiqun Cao; Wenjun Yang; Ping Gong (PLoS ONE, 2025)
Microorganisms play a central role in driving the biogeochemical cycles in lakes (reservoirs). This study aims to refine the microbial-driven nitrogen cycle processes in the sediments of the Three Gorges Reservoir and assess the overall state of nitrogen cycling within these sediments. The study focuses on the Three Gorges Reservoir as the research area, using metagenomic sequencing as a research method and measuring various environmental factors in the sediment of the region, systematically investigates the nitrogen cycle microorganisms and corresponding functional gene abundance characteristics attached to sediments from upstream, midstream, and downstream areas within the region, and explores key factors that may influence the composition of nitrogen cycle microbial communities. The outcomes of the present study manifest that within the sediments of the Three Gorges Reservoir, seven principal nitrogen cycling pathways exist. These pathways are specifically nitrogen fixation, nitrification, denitrification, nitrogen transport, organic nitrogen metabolism, assimilatory nitrate reduction, and dissimilatory nitrate reduction. Furthermore, the results of this study also reveal that the anaerobic ammonium oxidation genes are barely present in the sediments of this region, which indicates that the probability of the occurrence of anaerobic ammonium oxidation reactions in this area is negligible. The abundance of nitrogen cycle related functional genes and the diversity, composition and community structure of nitrogen cycling microorganisms differ among the upstream, midstream, and downstream regions. This suggests that as sediment particle size decreases along the course from the upstream to the downstream, it may have an impact on the distribution and community structure of nitrogen cycling microorganisms.